1985
DOI: 10.1128/jcm.22.3.416-418.1985
|View full text |Cite
|
Sign up to set email alerts
|

Production of 14C-labeled gas in BACTEC Neisseria Differentiation kits by Neisseria cinerea

Abstract: Six strains of Neisseria cinerea were tested in BACTEC Neisseria Differentiation kits (Johnston Laboratories, Inc., Towson, Md.), and all yielded positive glucose growth indices and negative maltose and fructose growth indices. These results were similar to those achieved with Neisseria gonorrhoeae. However, most of the N. cinerea isolates tested yielded 3-h glucose growth indices that were lower than those obtained with gonococci. 14C-labeled gas was produced significantly faster (P < 0.02) by N. gonorrhoeae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the past few years, reports of various rapid tests for the culture confirmation of Neisseria gonorrhoeae have appeared. However, decreased specificity (1)(2)(3)6), mainly due to cross-reactions with Neisseria cinerea, has been a problem with many of the tests. In an earlier study (4), we reported the sensitivity and specificity of the original Phadebact Gonococcus Test to be 94.3 and 100%, respectively.…”
mentioning
confidence: 99%
“…In the past few years, reports of various rapid tests for the culture confirmation of Neisseria gonorrhoeae have appeared. However, decreased specificity (1)(2)(3)6), mainly due to cross-reactions with Neisseria cinerea, has been a problem with many of the tests. In an earlier study (4), we reported the sensitivity and specificity of the original Phadebact Gonococcus Test to be 94.3 and 100%, respectively.…”
mentioning
confidence: 99%
“…In contrast, some strains of N. cinerea traditionally considered to be glucose negative (58,95) have given positive glucose reactions in some rapid tests (18,34,63). Studies have shown that strains of N. cinerea do produce carbon dioxide from glucose (17). It is possible that these strains produce acid from glucose but rapidly overoxidize it to carbon dioxide; the weak reaction in glucose may be due to the accumulation of a small amount of acid or to acidification caused by the formation of carbonic acid.…”
Section: Rapid Tests For Identification Of Neisseria Andmentioning
confidence: 99%
“…Perhaps in part because of the infrequency with which N. cinerea is isolated in the clinical laboratory, care must be taken not to identify this organism as N. gonorrhoeae (1,2,4,5). Laboratory technicians must be familiar with the limitations of the various rapid identification kits used to identify Neisseria species, especially when these isolates are cultured from nongenital sites.…”
mentioning
confidence: 99%